2022
DOI: 10.3847/1538-4357/ac778a
|View full text |Cite
|
Sign up to set email alerts
|

Doppler-velocity Drifts Detected in a Solar Prominence

Abstract: We analyzed multiline observations of a quiescent prominence from the slit spectrograph located at the Ondřejov Observatory. Dopplergrams and integrated intensity maps of the whole prominence were obtained from observations in six spectral lines: Ca ii H, Hϵ, Hβ, He i D3, Hα, and Ca ii IR. By combining integrated intensity maps with non-LTE radiative-transfer modeling, we carefully identified areas in an optically thin regime. The comparison of the Doppler-velocity maps and scatterplots from different lines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…The maximum drift velocities found in our simulation are of the order of 1 km s −1 . Similar values have been reported in other studies of partially ionized plasmas in different scenarios of the solar atmosphere, such as numerical simulations of the RTI (Popescu Braileanu et al 2021b) or observations of solar prominences (Khomenko et al 2016;Anan et al 2017;Stellmacher & Wiehr 2017;Wiehr et al 2019Wiehr et al , 2021González-Manrique et al 2022;Zapiór et al 2022). Therefore, the combination of numerical simulations and observations offers a coherent picture of the evolution of the partially ionized plasmas in coronal structures such as prominences or coronal rain blobs: while the various components of the plasma approximately behave as a single fluid in the central and denser regions of these structures, important differences in the motions of the charged and the neutral species ap- pear at the edges.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The maximum drift velocities found in our simulation are of the order of 1 km s −1 . Similar values have been reported in other studies of partially ionized plasmas in different scenarios of the solar atmosphere, such as numerical simulations of the RTI (Popescu Braileanu et al 2021b) or observations of solar prominences (Khomenko et al 2016;Anan et al 2017;Stellmacher & Wiehr 2017;Wiehr et al 2019Wiehr et al , 2021González-Manrique et al 2022;Zapiór et al 2022). Therefore, the combination of numerical simulations and observations offers a coherent picture of the evolution of the partially ionized plasmas in coronal structures such as prominences or coronal rain blobs: while the various components of the plasma approximately behave as a single fluid in the central and denser regions of these structures, important differences in the motions of the charged and the neutral species ap- pear at the edges.…”
Section: Discussionsupporting
confidence: 87%
“…Recent studies by S. J. González-Manrique et al (2022, in preparation) and Zapiór et al (2022) also point to the existence of large drift velocities (of up 1.7 km s −1 ) in small regions of solar prominences. Regarding coronal rain observations, Ahn et al (2014) compared the Doppler velocities computed from the spectral lines Hα and Ca II 8542 Å and found that they "matched well", although their results show that they are not completely identical.…”
Section: Introductionmentioning
confidence: 89%
“…These ion properties consist a set of solar observables, while observational techniques for neutrals require further developments (Khomenko et al 2016). However, see Zapiór et al (2022) for the recent report on ion-neutral velocity drift observed in a solar prominence.…”
Section: Physical Model and Governing Equationsmentioning
confidence: 99%
“…Figures 4 and 5 illustrate the comparison between different approaches for averaging drift velocities. In observational studies [11][12][13][14][15][16], velocities are derived from spectral lines of neutral and ionized elements. Due to the finite spatial resolution, the spectral signal in an observational pixel, emanating from an optically thin plasma, is a blend of signals along the line of sight and across the horizontal surface of the pixel.…”
Section: Ion-neutral Drift Signaturesmentioning
confidence: 99%
“…However, the spatial resolution, limited either by instrument capabilities or atmospheric seeing conditions, hinders the detection of the finest structures. Numerous authors have endeavoured to identify potential dynamical decoupling between plasma components by measuring sets of ionized and neutral spectral lines targeting optically thin prominence plasma [11][12][13][14][15][16]. Despite inherent uncertainties in these observations, straining the sensitivity limits of the instrumentation used, all studies, except [12], have reported a slight excess in the amplitude of ion variations over neutrals.…”
Section: Introductionmentioning
confidence: 99%